Analisis Perencanaan Anggaran Terhadap Penyerapan Anggaran Belanja Dinas Perumahan dan Kawasan Permukiman, Pertanahan dan Pertamanan Kota Bandung Tahun Anggaran 2019 - Debby Veramitha F; Sulistia Suwondo (Jurusan Akuntansi Politeknik Negeri Bandung, 2022)
The budget functions as planning and control related to plans and targets achieved by the government so that later expenditures can be accounted for to the public. Local governments make APBD as guidelines in regulating revenues and expenditures to carry out regional development so as to minimize deflections that will harm the state. There are However, several issues with its execution in budget absorption, especially in less than optimal spending. In 2019 the Housing and Settlement Areas, Land and Landscaping Services of Bandung City, the absorption of the goods and services budget has still not reached the predetermined target, notably in the execution of the program budget in 2019, when the absorption rate was less than 67%. Factors in budget planning that influence budget absorption in programs are administrative, activity program planning, regulatory, and internal.